From a crisis of results to a crisis of wellbeing – education reform and the declining sense of school belonging in Sweden. Issue 1 (2nd January 2023) - Högberg, Björn; Lindgren, Joakim
ABSTRACT: In response to declining results in the Programme for International Student Assessment (PISA) surveys, the then governing Swedish coalition in 2010–2014 introduced earlier grading, more extensive national testing and a new standards-based curriculum. These reforms coincided with a greater emphasis on inclusive' education understood in the 'narrow' sense of placement in mainstream schools. The combination of these two sets of reforms presents an interesting national case where traditional conservative demands for a core curriculum, testing and accountability were combined with calls to increase educational opportunity. Combining different methods and analysis of five separate waves of PISA data, we show that the reforms coincided with a decline in the sense of school belonging among pupils that was exceptional compared to other high-income countries, and especially among marginalised pupils. The study adds to the cumulative work of previous studies on policy effects on wellbeing, concluding that the Swedish compulsory school went from undergoing a mediatised results crisis to a mental health crisis among pupils.